Total phenols and flavonoids and antioxidant activity of Lampaya medicinalis F. Phil. leaf extracts - Gabino Garrido; Macarena Ortiz; Patricia Pozo (GarVal Editorial Ltda., 2013)
Context: Lampaya medicinalis F. Phil. (Verbenaceae) is a plant that grows in northern of Chile and it is used in ethnomedicine to treat bone pain, as an analgesic, in kidney ailments, disorders of the prostate, liver disease and dyspepsia, although there are few scientific studies about it. Aims: To determine the antioxidant activity of different extracts from leaves of L. medicinalis. Methods: Extractive methods were performed in water and methanol maceration, decoction and infusion from leaves of L. medicinalis. Phenols and flavonoids were measured and evaluated the total antioxidant capacity in vitro by discoloration radical 1,1-diphenyl-2-picrylhydrazyl (DPPH) and inhibition of the enzyme xanthine oxidase (XO). Results: The L. medicinalis extract, obtained by maceration in methanol (LM-M), showed higher concentrations of phenols (5807.9 ± 340.0 mg of gallic acid equivalents/100 g dry sample), while the decoction (LM-Dx) showed higher concentration flavonoids (136.0 ± 5.5 mg of quercetin equivalents/100 g dry sample) with statistically significant differences (p <0.05) relative to the other extracts. Moreover, the best results for the DPPH method were to the extracts LM-M and LM-Dx (IC50 = 24.9 ± 3.6 and 24.1 ± 2.7 μg/mL, respectively), without significant differences between them (p> 0,05). However, extracts had no activity on XO. Conclusions: Polar extracts from leaves of L. medicinalis show antioxidant activity due to the presence of flavonoids and phenols that could justify the ethnomedical use of the plant in pathologies transiting by a component of oxidative stress.